2006
DOI: 10.1111/j.1600-0447.2005.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental distress in the Danish general population

Abstract: The SCL mean scores of the Danish general population were relatively high, but similar to data from the Nordic countries. Consequently, interpretation of the Danish SCL requires Danish norms and Danish cut-off scores for caseness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
135
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(154 citation statements)
references
References 18 publications
17
135
2
Order By: Relevance
“…A negative correlation between social class and SCL score, i.e. a higher psychological well-being in the upper class, has previously been reported in a study on mental distress in the Danish general population (16). However, no correlations between social class and total SCL score were observed for the 46,XX-and 46,XY-virilized females and the CAH females in the present study (data not shown).…”
Section: Scl-90-r Scorescontrasting
confidence: 53%
“…A negative correlation between social class and SCL score, i.e. a higher psychological well-being in the upper class, has previously been reported in a study on mental distress in the Danish general population (16). However, no correlations between social class and total SCL score were observed for the 46,XX-and 46,XY-virilized females and the CAH females in the present study (data not shown).…”
Section: Scl-90-r Scorescontrasting
confidence: 53%
“…The psychometric analysis by the Mokken item response theory model has shown that the total score of the clinician rated HAM-D 6 (Bech 2008b) as well as the self-rating version of HAM-D 6 (Bech et al 2009) obtained Loevinger coeYcients of homogeneity above 0.50. When re-analyzing our Danish general population study (Olsen et al 2006) focusing on the SCL-6 depression subscale a coeYcient of homogeneity of 0.59 was obtained which is rather similar to that obtained in the present study (0.68). Concerning our baseline proxy, this four-item scale covers the SCL-6 depression scale to a large extent but lacks the item of depressed mood which is obviously a core item of depressive states (Bech 2008a).…”
Section: Methodological Considerationsmentioning
confidence: 56%
“…Occupational position was measured by self-report, yielding the following categories: (1) High-grade nonmanual worker (i.e., having supervisory function), (2) lowgrade non-manual worker (i.e., not having supervisory functioning), (3) skilled manual worker, (4) unskilled manual worker, (5) high-grade self-employed (i.e., with more than three employees), (6) low-grade self-employed (i.e., with 0-3 employees), and (7) unemployed (Derogatis 1994;Olsen et al 2006).…”
Section: Measurementsmentioning
confidence: 99%
“…We have previously reported indicators of mental distress in a random sample of Danish residents (Olsen et al 2006). The aim of the present study is to use these data to analyze the distribution of depressive, anxiety, and somatization symptoms, across different occupational positions.…”
Section: Introductionmentioning
confidence: 99%